Literature Review: Supplementary Food For Anemia Pregnant Women And Chronic Energy Deficiency Pregnant Women - Irfan Nafis Sjamsuddin; Divia Alfianita; Tuti Surtimanah (Jurnal Publikasi Kesehatan Masyarakat Indonesia, 2022)
One of the causes of stunting is anemia in pregnant women and Chronic Energy Deficiency (CED) in pregnant women, due to insufficient food intake. Various foods to increase hemoglobin, body weight, and Upper Arm Circumference (UAC) of pregnant women were studied. The aim was to determine the various types of food additives to increase the hemoglobin (Hb) of anemic pregnant women or to increase the UAC and body weight of CED pregnant women. The research method is a literature review by searching online databases through Google Scholar and PubMed obtained 13 food supplement articles for anemia pregnant women and 11 food supplement articles for CED pregnant women. Data processing and analysis by reading, and synthesizing research results using an article summary matrix, then identifying themes and combining the same themes. The results showed the supplementary foods that increase Hb were seaweed juice, Ebi cassava chips, green bean extract, moringa biscuits, otak-otak Tempe Bilis, and green spinach extract. Meanwhile, additional food consumed with iron tablets is dragon fruit juice, guava juice, dates, tempeh milk, green bean pudding, honey, and cavendish. Supplementary food to increase body weight and UAC from CED pregnant women are anchovy biscuits, anchovy biscuits mixed with moringa leaf flour, biscuits mixed with corn flour – soybeans – pumpkin – katuk leaves – powdered sugar – chicken eggs, bread/sandwich biscuits made from wheat, vegetable fat without hydrogenation, sugar, milk, eggs, nuts, dried fruit, fortified with vitamins and minerals, biscuits mixed with soy flour – wheat – sugar – skimmed milk – eggs – margarine, anchovy biscuits – moringa flour, dry food from flour soybeans – corn, Tempe flour cookies plus papaya and passion fruit juice, mackerel fish buns, pre-made biscuits. Health workers and health volunteers are expected to disseminate information on types of supplementary food to pregnant women through various methods and media including social media and demonstrate how to make processed food so that they are encouraged to practice it. All types of processed food additives have the potential to become a healthy food home industry.